Role of Jalauka Avcharana and Ayurvedic Management in Dadru Kushtha - Ajay Pratap Singh; Nandini Shah (International Journal of Ayurveda and Pharma Research, 2025)
A massive increase in incidence of skin problems can be seen in tropical and developing countries like India. Dadru (Tinea corporis) is one of the most encountered skin diseases occurring due to unhygienic conditions, poverty, poor sanitation, sun exposure etc. Dadru is described under Kshudra kushtha in Charaka Samhita, which if left untreated it seeps into deeper tissues and becomes difficult to cure. For present study, a male patient of 15 yrs age visited department of Shalya tantra at Uttarakhand Ayurved University Gurukul Campus Haridwar with complaint of widespread patches and severe itching over back side of neck from 6 months. He also had on and off constipation from 15 days, disturbed sleep for 2 months and loss of appetite. There was no significant past history of any other chronic disorder. The patient was diagnosed with Dadru kushtha (Tinea corporis) on the basis of clinical symptoms and investigations. Patient was treated with Ayurvedic para surgical process (Jalaukavchran) along with oral Ayurvedic medicines like Arogya vardhni vati, Nimbadi churna, Gandhak bhasma, Trikatu churna, Khadirarishta, Triphala churna for 45 days. A significant response was observed over clinical symptoms, healing and recovery of Dadru.